Burden of diet-related chronic diseases in Chinese and Japanese adults attributable to dietary risk factors from 1990 to 2021: a systematic analysis of the Global Burden of Disease Study 2021 - Wang, Minyan; Ma, Huan; Qin, Chu; Mandizadza, Oscar Onayi; Ni, Haojie; Shi, Yun; Ji, Conghua (Frontiers in Nutrition, 2025)
BackgroundChronic diseases are a major cause of death, contributing significantly to the global disease burden. The growing aging population and chronic disease burden in China and Japan have a substantial impact on health outcomes. Dietary factors, as key modifiable elements, are particularly important. Therefore, we aimed to analyze and compare the impact of dietary factors on the burden of chronic diseases in China and Japan and to develop measures to reduce this burden.MethodsAccording to the WHO classification of chronic diseases, we selected cardiovascular diseases, neoplasms, and diabetes for analysis. We collected relevant data from the GBD database, described and analyzed the disease burden by age, gender, and year, and created bar and trend charts. We conducted a comparative analysis of the dietary factors influencing these three chronic diseases by generating heatmaps. The joinpoint model was used to analyze the time trends of these three diseases from 1990 to 2021.ResultsFrom 1990 to 2021, the burden of neoplasms and cardiovascular diseases in China and Japan declined to varying degrees, while the burden of diabetes continued to increase. The main dietary risk factor for neoplasms is a high red meat diet, while for cardiovascular diseases, a high-sodium diet, especially in China. In addition, high meat consumption appears to serve as a protective factor for both Chinese and Japanese populations. Regarding dietary risk factors for diabetes, China is associated with a high red meat diet, whereas Japan is characterized by a high-processed meat diet.ConclusionBy comparing the burden of chronic diseases related to dietary factors in China and Japan, this study proposes strategies for national healthy diets, such as reducing sodium, processed meat, and red meat intake and increasing whole grains, vegetables, and fruit intake. In addition, attention should be given to the dietary status of the elderly, along with targeted health education initiatives.